Natural Killer Cells from Malignant Pleural Effusion Are Endowed with a Decidual-Like Proangiogenic Polarization - Annalisa Bosi; Silvia Zanellato; Barbara Bassani; Adriana Albini; Alessandra Musco; Maria Cattoni; Matteo Desio; Elisa Nardecchia; Davide Giuseppe D’Urso; Andrea Imperatori; Lorenzo Dominioni; Douglas M. Noonan; et al. (Journal of Immunology Research)
Natural killer (NK) cells are crucial in tumor recognition and eradication, but their activity is impaired in cancer patients, becoming poorly cytotoxic. A particular type of NK cells, from the decidua, has low cytotoxicity and shows proangiogenic functions. We investigated whether NK cells from peripheral blood (PB) and pleural effusions of patients develop decidual-like NK phenotype and whether exposure to IL-2 can restore their killing ability in the presence of pleural fluids. NK cells from pleural effusion of patients with inflammatory conditions (iPE, n = 18), primary tumor (ptPE, n = 18), and metastatic tumor (tmPE, n = 27) acquired the CD56brightCD16− phenotype. NK cells from both ptPE and tmPE showed increased expression for the CD49a and CD69 decidual-like (dNK) markers and decreased levels of the CD57 maturation marker. NK from all the PE analyzed showed impaired degranulation capability and reduced perforin release. PE-NK cells efficiently responded to IL-2 stimulation in vitro. Addition of TGFβ or cell-free pleural fluid to IL-2 in the culture medium abrogated NK cell CD107a and IFNγ expression even in healthy donors (n = 14) NK. We found that tmPE-NK cells produce VEGF and support the formation of capillary-like structures in endothelial cells. Our results suggest that the PE tumor microenvironment can shape NK cell polarization towards a low cytotoxic, decidual-like, highly proangiogenic phenotype and that IL-2 treatment is not sufficient to limit this process.